Flood risk assessment of environmental pollution hotspots. (February 2018) - Arrighi, Chiara; Masi, Matteo; Iannelli, Renato
Abstract: The potential spread of pollutants stored in environmental hotspots such as wastewater treatment plants, waste handling facilities, contaminated sites, etc., is among the adverse consequences of floods. This aspect has been rarely examined with a risk-based approach, although required by the European legislation. In this study, a method for estimating flood risk caused by environmental hotspots is developed. Risk includes flood hazard, hotspots exposure, and the expected severity of the environmental impacts, obtained as the combination of vulnerability of the surrounding environment and pollution potential of the hotspots. The assessment is performed at catchment scale on a geographical basis, using open data, available from databases of public bodies and environmental agencies. Risk maps obtained by the application of the developed method are produced for the Arno river catchment in Tuscany (central Italy). The area hosts approximately 1750 environmental pollution hotspots among which 5–10% have been classified at high risk. Highlights: A methodology is proposed to assess environmental impacts of floods. Hotspots are wastewater treatment plants, waste facilities and contaminated sites. Vulnerability combines pollution potential and environmental susceptibility. Priorities of intervention are identified at catchment scale.